If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -24 = 6x Reorder the terms: -24 + 2x = 6x Solving -24 + 2x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -24 + 2x + -6x = 6x + -6x Combine like terms: 2x + -6x = -4x -24 + -4x = 6x + -6x Combine like terms: 6x + -6x = 0 -24 + -4x = 0 Add '24' to each side of the equation. -24 + 24 + -4x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -4x = 0 + 24 -4x = 0 + 24 Combine like terms: 0 + 24 = 24 -4x = 24 Divide each side by '-4'. x = -6 Simplifying x = -6
| 8x+82=3x+2 | | 6ln(x^2-3)-7=12.2 | | 7+18r-3=6r+64-3r | | -12x-114=5x+11+8x | | -x^2-x+2=3x^2+10x+8 | | 8(y-3)=3y-59 | | 6(m-1/9)=55/12 | | x-4y=-25 | | 18-c+36=49 | | x+(x+35)+(2x-39)=592 | | 2(4d-6)=5d+12 | | x+13+1=44 | | 4k+4=2(k+5) | | 2/3x+1/9y=-19/27 | | 2.5x+10=1.5+17 | | 2r+4r=12 | | x+(x+100000)=600000000 | | 4y-19-y=-59+y | | -6-8(x+7)=-32-2x | | z/8=-6 | | -7x+26=6x | | 2x^3-19=12x | | x+13=44 | | (x^3+5x-18)/(x-2) | | W+15-28+5=177 | | -47-2x=7x+21 | | x-7=-x-3 | | 9c-11=7c+5 | | 12y^2-10y= | | -6(2b+2)+(13b-2)=0 | | 8-8x=18-15x | | r^2-5r-18=0 |